2013
DOI: 10.1063/1.4821078
|View full text |Cite
|
Sign up to set email alerts
|

Observation of superfluidity in two- and one-dimensions

Abstract: Even though there is no long-range-ordered state of a superfluid in dimensions lower than the threedimension (3D) such as bulk 4 He liquid, superfluidity has been observed for flat 4 He films in 2D and recently for nanotubes of 4 He in 1D by the torsional oscillator method. In the 2D state, in addition to the superfluid below the 2D Kosterlitz-Thouless transition temperature T KT , superfluidity is also observed in a normal fluid state above T KT , which depends strongly on the measurement frequency and the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…13 It has also been demonstrated that the superfluid onset temperature increases as the diameter of the channel decreases. 14,15 Another peculiar phenomenon is observed when liquid 4 He is added to a small bowl below 2.17 K: a thin invisible film creeps up the inside wall of the bowl and down on the outside. A drop forms from this film and falls off outside the bowl until it is empty, demonstrating that the film behaves like a superfluid confined in a nanochannel (Fig.…”
Section: Superfluid: From Atoms To Molecules and Ionsmentioning
confidence: 99%
“…13 It has also been demonstrated that the superfluid onset temperature increases as the diameter of the channel decreases. 14,15 Another peculiar phenomenon is observed when liquid 4 He is added to a small bowl below 2.17 K: a thin invisible film creeps up the inside wall of the bowl and down on the outside. A drop forms from this film and falls off outside the bowl until it is empty, demonstrating that the film behaves like a superfluid confined in a nanochannel (Fig.…”
Section: Superfluid: From Atoms To Molecules and Ionsmentioning
confidence: 99%
“…For a film, the effective length L eff = z /(n 1 a 2 ) ∼ L z /L x ∼ z / x , i.e., the aspect ratio of the anisotropic lattice, because n 1 = N/ z = N L /(2 z ) and L α ∼ α /a (α = x and z). Experimentally, the aspect ratio L z /L x can be estimated to be 15−50 [4,6,7,11,13,17]. On the other hand, to simulate 4 He atoms filling nanopores, we consider an anisotropic three-dimensional cubic lattice, i.e., a bar, composed of…”
Section: A Model Without Phase Slippagementioning
confidence: 99%
“…To simulate 4 He atoms adsorbed on the inner walls of nanopores [4,6,7,11,13,17], we consider an anisotropic two-dimensional square lattice, i.e., a film, composed of L x × L z sites with L z L x (see Fig. 1).…”
Section: A Model Without Phase Slippagementioning
confidence: 99%
See 2 more Smart Citations